The Forms of Traditional Javanese Games as a Medium for Character Education for Elementary School Students: Bentuk Permainan Tradisional Jawa Sebagai Media Pendidikan Karakter Siswa SD - Apriliana, Salsabila; Setiawaty, Rani; Achmad, Ayu Widia; Widayanti, Destia Irma; Antawinata, Ririn (DIKODA JURNAL PENDIDIKAN SEKOLAH DASAR, 2025)
The planting of character values is important for the formation of a child's personality. Using a systematic literature review (SLR) method, the aim of this research is to explain the types of traditional Javanese games that can be used to teach character to elementary school students. Several inclusion criteria were used to select 20 relevant scientific articles. The data for this research consists of 20 articles collected through the 'Google Scholar' application. The analysis results show that character values such as honesty, responsibility, cooperation, discipline, and love for local culture are instilled in traditional games such as gobak sodor, engklek, dakon, and egrang. These games enhance children's social and moral skills naturally, aside from being mere entertainment.